THE CRIMINAL JURIDICAL DOGMATICS - Rodríguez Medina, José Luis (2021)
This essay proposes a response to the ambiguous aspects in the conceptual, historical and methodical characteristics of this famous criminal legal science, taking into consideration that in an acquiescent and instituted way, the criminal legal dogmatics and its exegetical determination of the criminal pragmatic devices in its once a conception, in the mutual symbiosis of rights and their restrictions, has ceased to be a mere institution ofsynthetic extensions and hasbecome an authentic legal tool that is oriented towards hermeneutics, systematization, development of normative canons, convictions and judgments of a scientific nature in the sphere of criminal law, all this, with the teleological conception of providinglegal security in the normative order, in the paradigm of a constitutional state of law. This legal science raises relatively complex questions, both in its historical evolution, its content, its methods and its exegetical projection in the field of crimetheory and punitive axioms. Added to this is the fact that dogmatics contributes to coherence in the internal and external justification of judicial decisions, beyondthe intrinsic value of the search for judicial decisions validated in law; It is in merit to this that, in orderto have a clear perception and understanding of this science, it is necessary to carry out this essay in order to elucidate these substantial issues for the field of law, taking into consideration the aposteriori studies already proclaimed. in the field of law